A combined sleep hygiene and mindfulness intervention to improve sleep and well-being during high-performance youth tennis tournaments - Lever, J. R.; Murphy, A. P.; Duffield, R.; Fullagar, H. H. K. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate the effects of combined sleep hygiene recommendations and mindfulness on actigraphy-based sleep parameters, perceptual well-being, anxiety, and match outcomes during high-performance junior tennis tournaments. Methods: In a randomized crossover design, 17 high-performance junior tennis players completed the baseline, control, and intervention (INT) conditions across 3 separate weeks. The baseline consisted of unassisted, habitual sleep during a regular training week, and the control was unassisted sleep during a tournament week. The players attended a sleep education workshop and completed a nightly sleep hygiene protocol during a tournament week for the INT. Analysis was performed on the weekly means and on the night prior to the first match of the tournament (T-1). Results: Significant differences were observed for increased time in bed, total sleep time, and an earlier bedtime (P < .05) across the INT week. These parameters also significantly improved on T-1 of the INT. A moderate effect size (P > .05, d > 1.00) was evident for decreased worry on T-1 of the INT. Small effect sizes were also evident for improved mood, cognitive anxiety, and sleep rating across the INT week. The match performance outcomes remained unchanged (P > .05). Conclusions: Sleep hygiene INTs increase the sleep duration of high-performance junior tennis players in tournament settings, including the night prior to the tournament`s first match. The effects on perceptual well-being and anxiety are unclear, although small trends suggest improved mood, despite no effect on generic match performance outcomes.